Tuning the Photophysical Properties of Spirolactam Rhodamine Photoswitches. Issue 3 (26th November 2020) - Li, Bo; Haris, Uroob; Aljowni, Maha; Nakatsuka, Andrew; Patel, Shreya K.; Lippert, Alexander R.
Abstract: Spirolactam rhodamines are fluorescent photoswitches that are useful for single molecule localization microscopy, volumetric 3D digital light photoactivatable dye displays, and other applications. Measurement of the photophysical properties, particularly photoswitching kinetics and quantum yields, is challenging and a comprehensive understanding of how molecular structure affects these parameters remains incomplete. In this study, we have synthesized a series of N ‐aryl spirolactam rhodamine photoswitches with fluorescent emissions at 585 nm and 518 nm. Extinction coefficients and fluorescence quantum yields of the fluorescent form of the photoswitch have been measured using excess trifluoroacetic acid to drive the equilibrium to the open form. A method to determine photoswitching kinetics and quantum yields was developed by monitoring the kinetics to reach equilibrium between the on‐state and off‐state and fitting this data to a rate equation for a reaction in equilibrium. Trends based on the electronic and steric properties of the aryl substituents were evaluated. Using this information, a proof‐of‐principle demonstration of 3D voxel formation was accomplished using a green (518 nm) emitting photoswitch, setting the foundation for a multi‐colour volumetric 3D display. Abstract :